PENGARUH STRATEGI PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Mashadi; Abbas Sofwan; Jauhar Fuad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in Islamic Religious Education learning due to conventional learning strategies applied by teachers and lack of learning motivation. This research uses quantitative research with the type of One Group Pretest-Posttest Design. The results of the study indicate that: (1) There is a positive and significant influence between learning strategies on the learning outcomes of Islamic Religious Education of Students at SMPN 2 Wates Blitar. (2) There is a positive and significant influence between learning motivation on the learning outcomes of Islamic Religious Education of Students at SMPN 2 Wates Blitar. (3) There is a positive and significant influence between learning strategies and learning motivation on the learning outcomes of Islamic Religious Education of Students at SMPN 2 Wates Blitar. Every increase in the variables of learning strategies and learning motivation will increase the learning outcomes of Islamic Religious Education of Students at SMPN 2 Wates Blitar, and vice versa.